2015
DOI: 10.5664/jcsm.4526
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Pattern in Charcot-Marie-Tooth Disease Type 2: Report of Family Case Series

Abstract: Taken together, these data show that CMT2 disease is characterized by important changes in sleep architecture, probably due to sleep fragmentation. Although these alterations may worsen with disease severity, it seems that they are not related to sleep breathing or movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
2
7
1
Order By: Relevance
“…In the previous study conducted by our group, individuals with CMT type 2 showed similar results, with increased WASO, indicative of sleep fragmentation, and changes in sleep architecture 9 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the previous study conducted by our group, individuals with CMT type 2 showed similar results, with increased WASO, indicative of sleep fragmentation, and changes in sleep architecture 9 .…”
Section: Discussionsupporting
confidence: 74%
“…Besides, we demonstrated that patients with CMT type 2 present higher fragmentation of sleep 9 , but there is no evidence so far about the relationship of these modifications with pain perception and nocturnal cramps.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“… 56 A number of small reports describe symptoms of dyspnea, dysphagia, and obstructive sleep apnea, laryngoscopic evaluation of the upper airway, as well as treatment with continuous or bi-level positive airway pressure. 55 , 57 62 While there is not enough evidence to make recommendations regarding clinical screening for sleep and respiratory disorders, longitudinal care should optimally address these potential comorbidities.…”
Section: Clinical Surveillance Of Comorbidities Complications and Mmentioning
confidence: 99%
“…Previous studies have described excessive diaphragmatic dysfunction and other respiratory muscles in the CMT patients including severe cases of respiratory failure as a result of diaphragmatic paresis [13,14]. …”
Section: Introductionmentioning
confidence: 99%